2019
DOI: 10.1111/crj.13054
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and disease severity are among the determinants of quality of life in bronchiectasis

Abstract: Introduction Quality of life (QoL) is known to be impaired in patients with bronchiectasis, which is generally attributed to exacerbations and chronic pulmonary symptoms. The aim of this study was to determine if aetiology and disease severity are associated with QoL in bronchiectasis. Methods We conducted a retrospective analysis of clinical stable patients with bronchiectasis. Diagnostic workup into the aetiology of bronchiectasis was conducted according to the current guidelines. QoL was measured by QoL‐B q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Terpstra et al [20] reported signi cantly worse QoL in BE patients with COPD than in other BE patients. In their study population of 200 BE patients (aged 69.5 years), the mean number of exacerbations was one per year, with zero hospitalisations and a mean mMRC score of 2.68 (SD 1.09).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Terpstra et al [20] reported signi cantly worse QoL in BE patients with COPD than in other BE patients. In their study population of 200 BE patients (aged 69.5 years), the mean number of exacerbations was one per year, with zero hospitalisations and a mean mMRC score of 2.68 (SD 1.09).…”
Section: Discussionmentioning
confidence: 97%
“…The mean mMRC score in our population was 2.0, but there was a median of two exacerbations per year. Previously, BSI was proposed as a tool for scoring the severity of BE and FACED as a tool for predicting mortality [20] [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the QoL of bronchiectasis patients with COPD has rarely been evaluated. One European study analyzed bronchiectasis patients' QoL according to etiology, and patients with COPD-related bronchiectasis were shown to have lower QoL compared with patients with bronchiectasis caused by other etiologies ( 35 ). However, because that study evaluated QoL according to etiology, COPD patients whose COPD was not considered to be the cause of bronchiectasis were not included in the COPD group.…”
Section: Discussionmentioning
confidence: 99%
“…QoL-B respiratory symptoms domain was most commonly used in clinical trials and was able to discriminate patients based on demographics (Polverino et al, 2020), disease severity (Olveira et al, 2014a, Quittner et al, 2015, Visser et al, 2019Liu et al, 2019), exacerbations (Olveira et al, 2014a, Dhar et al, 2019, Visser et al, 2019, Brown et al, 2019, bacteriology (Olveira et al, 2014a, Terpstra et al, 2019, Dhar et al, 2019, Brown et al, 2019, Ewen et al, 2019, Asakura et al, 2020, sputum volume (Polverino et al, 2018, Dhar et al, 2019, dyspnoea (Dhar et al, 2019, haemoptysis (Olveira et al, 2014a) and exercise capacity (Quittner et al, 2015). Discriminant validity for the other 7 domains was also reported.…”
Section: Bronchiectasis Specific Hrqol Questionnairesmentioning
confidence: 99%
“…Discriminant validity for the other 7 domains was also reported. Studies reported that some of the QoL-B domain scores were able to discriminate patients based on demographics (Polverino et al, 2018, Olveira et al, 2014a, McCullough et al, 2011, Terpstra et al, 2019, disease severity (Dhar et al, 2019, Quittner et al, 2015, Olveira et al, 2014a, Visser et al, 2019, exacerbations (Dhar et al, 2019, Visser et al, 2019, Olveira et al, 2014a, Alcaraz-Serrano et al, 2020 and bacteriology (Polverino et al, 2018, Visser et al, 2019, Olveira et al, 2014a, Asakura et al, 2020, haemoptysis (Olveira et al, 2014a), dyspnoea (De Camargo et al, 2020), adherence to treatments (McCullough et al, 2014 and exercise capacity (Quittner et al, 2015). The BHQ was able to discriminate patients based on demographics (Choi et al, 2020, Diggins et al, 2020, disease severity, exacerbations and hospital admissions in the preceding 12 months (Spinou et al, 2017b).…”
Section: Bronchiectasis Specific Hrqol Questionnairesmentioning
confidence: 99%